Effect of Draw Resistance on Phenol and Its Contribution Degree of Cigarette Hazard Index - , Wang Hao; , Zhan Jianbo; , Yu Zhenhua; , Yu Yao; , Cheng Liang; , Yu Jiang; , Yue Baoshan; , Zhang Ying; , Li Muyan; , Ji Yafeng; , He Danfeng; , Chen Shuzong; et al. (Archives of Current Research International, 2016)
Effect of cigarette draw resistance between 860-1130Pa on deliveries of phenol in mainstream cigarette smoke（MCS）was investigated, and contribution degree of cigarette hazard index was proposed for the first time to study how the contribution degree could be affected by 7 harmful components. Effect of phenol with different draw resistance on contribution degree of cigarette hazard index was also studied. The results showed that contribution degree of phenol is uniform, which is different from variation of crotonaldehyde, HCN, CO and NNK, meanwhile, 1000Pa could be viewed as critical draw resistance, and there is an obvious mainstream cigarette smoke variation below and above 1000Pa. Analysis of contribution degree of cigarette hazard index separately is a feasible tool to study variation of smoke harmful components, which lays foundation for further changing trend and roles of different harmful components while the cigarette hazard index changes.